PENGARUH KERAGAMAN PRODUK DAN HARGA TERHADAP KEPUASAN PELANGGAN SERTA DAMPAKNYA TERHADAP LOYALITAS PELANGGAN MINIMARKET DI KOPERASI VISIANA BAKTI TVRI JAKARTA - Zelin Ferdias Capriati (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2023)
The research objective was to determine the effect of both partially and simultaneously the variety of products and prices on customer satisfaction, as well as to determine the effect of customer satisfaction on loyalty. This research is associative with a quantitative approach. The population in this study were all minimarket customers at the Visiana Bakti Cooperative TVRI Jakarta, while the sample used in this study was 100 respondents. Data collection techniques by way of questionnaires, and data analysis techniques using instrument tests, classical assumption tests, regression analysis, coefficient of determination, t test and F test. The results show that product diversity has a positive and significant effect on customer satisfaction. This can be proven based on the t valuecount 9.341 > ttable 1.984 with a significance of 0.000 <0.05. The simple linear regression equation Y=16.957+0.518X1, meaning that every one unit increase in product diversity will increase customer satisfaction by 0.518. The R Square of 0.471 means that product diversity (X1) contributes to the customer satisfaction variable (Y) of 47.1%. Price has a negative and significant effect on customer satisfaction. This can be proven based on the value of tcount -7.475 <ttable 1.984 with a significance of 0.000 <0.05. The simple linear regression equation Y=43.446 - 0.457X2 means that every price increases by one unit it will reduce customer satisfaction by -0.457 units. The R Square of 0.363 means that price (X2) contributes to the customer satisfaction variable (Y) of 36.3%. Product diversity and prices simultaneously have a positive and significant effect on customer satisfaction. This can be proven based on thecalculated 77.667 > Ftable 2.70 with a significance of 0.000 <0.05 and an R Square of 0.616, which means that product diversity (X1) and price (X2) simultaneously contributes to the customer satisfaction variable (Y) of 61.6%. Customer satisfaction has a positive and significant effect on customer loyalty. This can be proven based on the value of tcount 6.765 > ttable 1.984 with a significance of 0.000 <0.05. The simple linear regression equation Z = 8.102 + 0.420Y means that every time customer satisfaction increases by one unit, it will increase customer loyalty by 0.420 units. The R Square of 0.318 means that customer satisfaction (Y) contributes to the customer loyalty variable (Z) of 31.8%.